Analisis Puisi “Kesabaran” Karya Chairil Anwar Dengan Pendekatan Stuktural - Putri Kartini; Farhah Siti Kamila (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
The poem "Patience" by Chairil Anwar became one of the literary works that inspired many people. This poem describes one's patience and sincerity in facing life's trials. This paper aims to provide an appreciation analysis of the poem "Patience" by Chairil Anwar. This analysis is carried out by paying attention to the structure, language, and meaning contained in the poem. In this analysis, the writer finds that the structure of the poem "Patience" consists of four stanzas with each stanza consisting of four lines. In each of his verses, Chairil Anwar emphasizes the message of patience and sincerity in facing life's trials. The language used by Chairil Anwar in this poem is very effective in conveying philosophical messages about patience and sincerity. Chairil Anwar uses simple language but full of deep meaning. The meaning contained in the poem "Patience" is about one's patience and sincerity in facing life's trials. Chairil Anwar described that patience and sincerity are two very important things in life. Even though life is full of trials and tribulations, with patience and sincerity, humans are able to face all of that with steadfastness. It can be concluded that the poem "Patience" by Chairil Anwar is a very valuable literary work. This poem is able to describe philosophical messages about patience and sincerity in simple yet meaningful language. Through this poem, Chairil Anwar inspires readers to always be patient and stay strong in facing all of life's trials.